Orthodox, Social and Societal Marketing: the exchange of different relations with the society - Silva, Edson Coutinho da (2007)
The present article has the objective of emphasizing differences among the concepts of orthodox marketing, societal marketing and social marketing in order to clarify possible misunderstandings and indiscriminate use of them. We present here a historical approach to these different concepts, their practice and evolution within organizations.  Although the practice of marketing refers to the use of defined tools and objective that is the management of exchange, the marketing concept adopted influences outcomes. As a consequence, activities related to marketing should be developed considering these differentiations. This article does not have the pretension to discuss all about this subject but to provoke a debate about it. It intends to prevent proliferation of inadequate use of these referring terms according to their specific concepts that has contributed negatively to the process of teaching, learning, and practicing marketing in society.Key-words: Marketing. Societal marketing. Social marketing.